Risk Factors Affecting Non-Compliance of Drug Therapy Among Hypertensive Patients at Cherlapally, India - Dumpala, Suguna; Konagunta, Nagaraj; Venna, Guru Prasad (National Journal of Community Medicine, 2015)
Objective: Purpose of the study was to identify risk factors affect- ing the non-compliance of drug therapy among patients with hy- pertension. Methods: A Cross-sectional community based study was carried out among already diagnosed 300 hypertensive patients to assess non-compliance of drug therapy among patients with hyperten- sion. Primary outcome-non-compliance measured in percentages, proportions using chi-square; adjusted and unadjusted odds rati- os (ORs) based on logistic regression models were used for statis- tical analysis. Results: Total subjects who did not take antihypertensive medica- tion were 38 (13%). Non-compliance among Gender and occupa- tion groups was significant (p-value<0.05). Unadjusted analysis showed statistically significant association between noncompli- ance and Gender (OR of 2.444); Occupation (OR of 0.146) in de- pendents; (OR of 0.122) in unskilled and (OR of 0.143) in skilled workers; Co-morbidities (OR of 2.667); and Physical exercise (OR of 3.453) but adjusted analysis showed significant association be- tween noncompliance and gender only. Conclusions: Active patients’ collaboration for treatment compli- ance should be directed towards rural illiterates by primary health care providers.